Internet of Things: A Boon for Supply Chain Management - Satpathy, Diptikanta (Indian Journal of Computer Science, 2019)
Data is the the new oil. The more data one has, the more powerful one is. According to knowledge (DIKW) pyramid, wisdom helps move human race forward, but data is at the base of the pyramid. Internet of Things (IoT) is capable of collecting vast amount of real-time data through sensors and convert data into information. Information gives way to knowledge and wisdom. Technology is beneficial as it saves time and provides comfort. So, the Internet of Things (IoT) with its evolution is rapidly becoming a basic feature from an optional or luxury feature. Manufacturing, logistics, and supply chain enterprises are aggressively moving to embrace modern technologies. Internet of Things (IoT), Machine Learning (ML), Artificial Intelligence (AI), Cognitive Intelligence (CI), and Big Data (BD), and Robotic Process Automation (RPA) are all buzzwords of today's supply chain management. Among all, IoT and Big Data are two fields of technologies which seem to be evolving very fast. IoT in supply chain can help organizations manage their operations from production through to delivery. RFID, GPS, and IVMT provided real-time data is helping supply chain managers to take smart decisions. Cloud based IoT coupled with data analytics and big data is definitely the next big thing in supply chain management. IoT provides end-to-end visibility in a supply chain from manufacturing through to delivery, hence, it provides accessibility to real-time data, hence, enabling quick decision making based on variations. This article talks about applications of IoT with special focus on supply chain management.